The Effect of Microcosm Biofilm Decontamination on Surface Topography, Chemistry, and Biocompatibility Dynamics of Implant Titanium Surfaces - Sousa, Vanessa; Mardas, Nikos; Spratt, Dave; Hassan, Iman A.; Walters, Nick J.; Beltrán, Víctor; Donos, Nikolaos (MDPI AG, 2022)
Since the inception of dental implants, a steadily increasing prevalence of peri-implantitis has been documented. Irrespective of the treatment protocol applied for the management of peri-implantitis, this biofilm-associated pathology, continues to be a clinical challenge yielding unpredictable and variable levels of resolution, and in some cases resulting in implant loss. This paper investigated the effect of microcosm biofilm in vitro decontamination on surface topography, wettability, chemistry, and biocompatibility, following decontamination protocols applied to previously infected implant titanium (Ti) surfaces, both micro-rough -Sandblasted, Large-grit, Acid-etched (SLA)-and smooth surfaces -Machined (M). Microcosm biofilms were grown on SLA and M Ti discs. These were treated with TiBrushes (TiB), combination of TiB and photodynamic therapy (PDT), combination of TiB and 0.2%CHX/1%NaClO, plus or minus Ultraviolet-C (UV-C) radiation. Surface topography was evaluated by Scanning Electron Microscopy (SEM) and Laser Surface Profilometry. Surface function was analysed through wettability analysis. Surface chemistry evaluation of the discs was performed under SEM/Energy-dispersive X-ray spectroscopy (EDX) and X-ray photoelectron spectroscopy (XPS). Biocompatibility was tested with the cytocompatibility assay using human osteoblast-like osteosarcoma cell line (MG-63) cells. Elemental analysis of the discs disclosed chemical surface alterations resulting from the different treatment modalities. Titanium, carbon, oxygen, sodium, aluminium, silver, were identified by EDX as the main components of all the discs. Based on the data drawn from this study, we have shown that following the decontamination of Ti surfaces the biomaterial surface chemistry and topography was altered. The type of treatment and Ti surface had a significant effect on cytocompatibility (p = 0.0001). Although, no treatment modality hindered the titanium surface biocompatibility, parameters such as the use of chemical agents and micro-rough surfaces had a higher cytotoxic effect in MG-63 cells. The use of smooth surfaces, and photofunctionalisation of the TiO2 layer had a beneficial effect on cytocompatibility following decontamination.
Keywords: peri-implantitis; decontamination; therapy; UV-C; photodynamic therapy; titanium Brush; biocompatibility; XPS; EDX